The interplay between a Confucian-heritage culture and teachers’ sentiments and attitudes towards inclusion in Macao - Correia, Ana; Monteiro, Elisa; Kuok, Angus; Forlin, Christine; Teixeira, Vitor (European Journal of Special Education Research, 2019)

Catholic schools and inclusive education in Macao: a journey of a thousand miles - Correia, Ana; Teixeira, Vitor (EDUCA - International Catholic Journal of Education, 2017)
Publisher: EducA

"The will and the way of inclusive education in Macao", - Correia, Ana; Teixeira, Vitor (Asian Education and Development Studies, 2017)
1 citations (Crossref) [2022-09-21]

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

Inclusive education in Macao: Teachers' perceptions and attitudes - Correia, Ana; Teixeira, Vitor; Monteiro, Elisa; Kuok, A. C. H. (University of Saint Joseph, 2017)

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.
1 citations (Crossref) [2022-09-21]

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
9 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2018.1514762
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

Perceived competence and social acceptance of preschool children in Macao: a case study - Teixeira, Vitor; Correia, Ana (International Journal of Learning and Teaching, 2017)
0 citations (Crossref) [2022-09-21]

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
7 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2017.1414318
Keywords: Disability; education policy; inclusive education; special education; special education needs